2009
DOI: 10.1038/jes.2009.27
|View full text |Cite
|
Sign up to set email alerts
|

Indoor airborne fungi and wheeze in the first year of life among a cohort of infants at risk for asthma

Abstract: In studies worldwide, respiratory outcomes such as cough, wheeze and asthma have been consistently linked to mold exposure. Young children spend most of their time indoors and may be particularly vulnerable. We evaluated the associations between exposure to airborne fungal levels and episodes of wheezing in a cohort of 103 infants at risk for asthma (due to maternal history of asthma), living primarily in low-income urban settings. Using a new protocol that facilitates identification of rare and slow-growing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 54 publications
3
64
1
4
Order By: Relevance
“…DIJKSTRA [29] DALES [16] DALES [32] PONSONBY [18] ZHENG [27] CHEN [25] FREEMAN [20] FREEMAN substudy [20] SPENGLER [19] PEKKANEN [33] DONG [17] DONG [22] ANTOVA [15] WARMAN [24] Summary (OR FAGBULE [34] VERHOEFF [31] LI [26] LI [35] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] BRUNEKREEF [21] STRACHAN [37] STRACHAN [38] DIJKSTRA [29] DALES [16] SPENGLER [19] EMENIUS [36] ALPER [39] DONG [17] DONG [22] ANTOVA [15] ROSENBAUM [43] IOSSIFOVA [8] KARVONEN [42] Summary (OR LI [26] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] CHEN [25] BIAGINI [45] IBARGOYEN-ROTETA [44] KOSKINEN substudy [47] KOSKINEN [47] LI [26] LI [35] BRUNEKREEF [21] DONG …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DIJKSTRA [29] DALES [16] DALES [32] PONSONBY [18] ZHENG [27] CHEN [25] FREEMAN [20] FREEMAN substudy [20] SPENGLER [19] PEKKANEN [33] DONG [17] DONG [22] ANTOVA [15] WARMAN [24] Summary (OR FAGBULE [34] VERHOEFF [31] LI [26] LI [35] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] BRUNEKREEF [21] STRACHAN [37] STRACHAN [38] DIJKSTRA [29] DALES [16] SPENGLER [19] EMENIUS [36] ALPER [39] DONG [17] DONG [22] ANTOVA [15] ROSENBAUM [43] IOSSIFOVA [8] KARVONEN [42] Summary (OR LI [26] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] CHEN [25] BIAGINI [45] IBARGOYEN-ROTETA [44] KOSKINEN substudy [47] KOSKINEN [47] LI [26] LI [35] BRUNEKREEF [21] DONG …”
Section: Discussionmentioning
confidence: 99%
“…BRUNEKREEF et al [21] reported a significantly positive association between domestic mould and persistent wheeze in 12-yrold children. BELANGER et al [53] observed an increased risk among 1-yr-old children who were genetically predisposed to allergic diseases, while a second study found no association among children in the same age range (although this may have been due to inadequate power as the study included only 103 children) [43].…”
Section: Wheezementioning
confidence: 99%
See 2 more Smart Citations
“…are reported to be the most common indoor airborne fungi. 3,11e17 However, in the case of Cladosporium, because the indoor concentration is highly correlated with the outdoor concentration, 13 the primary source of Cladosporium is considered to be the outdoor environment. A recent environmental survey in Japan used an air sampler to investigate the profile of indoor airborne fungal spores.…”
Section: Indoor Environmental Fungimentioning
confidence: 99%